2010
DOI: 10.2134/agronj2010.0087
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production in Switchgrass across the United States: Database Description and Determinants of Yield

Abstract: Fundamental to deriving a sustainable supply of cellulosic feedstock for an emerging biofuels industry is understanding how biomass yield varies as a function of crop management, climate, and soils. Here we focus on the perennial switchgrass (Panicum virgatum L.) and compile a database that contains 1190 observations of yield from 39 fi eld trials conducted across the United States. Data include site location, stand age, plot size, cultivar, crop management, biomass yield, temperature, precipitation, and infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
210
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(231 citation statements)
references
References 39 publications
17
210
3
Order By: Relevance
“…A database of switchgrass studies from 39 field sites in 17 states supports a single harvest for bioenergy [56]. Harvesting after frost allows N and other nutrients to be mobilized into roots for storage during winter and use for new growth the following spring [50].…”
Section: Agronomics Of Perennial Grass Feedstocksmentioning
confidence: 99%
“…A database of switchgrass studies from 39 field sites in 17 states supports a single harvest for bioenergy [56]. Harvesting after frost allows N and other nutrients to be mobilized into roots for storage during winter and use for new growth the following spring [50].…”
Section: Agronomics Of Perennial Grass Feedstocksmentioning
confidence: 99%
“…Cultivars are classified into lowland and upland phenotypic groups, with both groups growing well throughout the switchgrass adaptation zone [33]. Lowland ecotypes tend to be more productive [5,31], but this advantage decreases with increasing latitude [4]. The ability to grow with low or little fertilizer inputs and less pesticide application provides economic and environmental advantages over annual crops that require annual seeding and fertilization [30], and that may provide less winter cover for soil and water conservation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mulkey et al [23] reported no benefit with N application rates above 56 kg ha −1 on switchgrass-dominated Conservation Reserve Program (CRP) lands in South Dakota. In an analysis of 19 switchgrass research publications in the literature, Wullschleger et al [34] noted that both upland and lowland switchgrass ecotypes responded to total N levels of approximately 100 kg N ha −1 ; however, in some cases, the 0 N control produced as much biomass as switchgrass treated with 100 kg N ha −1 . A major question regarding switchgrass management as a bioenergy crop is optimizing N application rate at the field scale since excessive N fertilization may result in adverse environmental and economic effects.…”
Section: Introductionmentioning
confidence: 99%